UTILIZATION OF BIOPULPING BLACK LIQUOR AS PRESERVATIVE TO FUNGAL ATTACK ON JABON WOOD (Anthocephalus cadamba Miq.) - Anita, Sita Heris; Fatriasari, Widya; Zulfiana, Deni (Teknologi Indonesia, 2014)
Biopulping black liquor, byproduct from biopulping process using white-rot fungi (Phanerochaete chrysosporium) that has been incubated for 30 and 45 days, was used as preservative of Jabon wood (Anthocephalus cadambaMiq.). The main objectives of this study was to investigate the effect of various dipping durations of preservative on absorption process into wood and the weight loss of un-preserved and preserved wood againts fungal attack. Preservation method used in this study was dipping method with various dipping durations (i.e. 10, 30, and 60 minutes) with triplicate. The result showed that dipping process of of Jabon wood into biopulping black liquor for 60 minutes demonstrated the highest retention, i.e.0.21 g/cm3. The weight losses suffered fom by un-preserved and preserved Jabon wood were 55.19% to 55.67% and 6.64% to 12.78%, respectively. Biopulping black liquor had improved the resistance of Jabon wood to both white-rot and brown rot fungi attacks compared to untreated wood sample.